1975
DOI: 10.5962/bhl.title.99728
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-nesting birds of Arizona and New Mexico forests /

Abstract: with central headquarters at Fort Collins, in cooperation with Colorado State University. Author is located in Tempe, in cooperation with Arizona State University. names of plants and animals and the scientific names when they were referred to in the references, or when they could be determined from the common name used. Unless otherwise noted, North American distribution is taken from Audubon Western Bird Guide (Pough 1957), Arizona distribution from The Birds of Arizona (Phillips et al. 1964), and New Mexico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Many species of birds are dependent on snags for nest sites, including 85 species of cavity-nesting birds in North America (Scott et al, 1977), and 31 cavity-nesting birds with ranges that include the Black Hills of South Dakota and Wyoming (South Dakota Ornithologists' Union, 1991). The presence and abundance of cavitynesting birds in managed ponderosa pine (Pinus ponderosa Laws.)…”
Section: Introductionmentioning
confidence: 99%
“…Many species of birds are dependent on snags for nest sites, including 85 species of cavity-nesting birds in North America (Scott et al, 1977), and 31 cavity-nesting birds with ranges that include the Black Hills of South Dakota and Wyoming (South Dakota Ornithologists' Union, 1991). The presence and abundance of cavitynesting birds in managed ponderosa pine (Pinus ponderosa Laws.)…”
Section: Introductionmentioning
confidence: 99%
“…In Arizona and New Mexico, ponderosa www.elsevier.com/locate/foreco Forest Ecology and Management 216 (2005) [227][228][229][230][231][232][233][234][235][236][237][238][239][240] pine (Pinus ponderosa) forests cover about 3.2 million ha (Klemmedson and Smith, 1979) and provide nesting habitat for more cavity-nesting species than any other forest type (Scott and Patton, 1989). Prior to 1870, tree densities were thought to average $60 ha À1 , with forests experiencing low intensity but high frequency (e.g., every 4 years) fires.…”
Section: Introductionmentioning
confidence: 99%
“…Snags are a focal point for wildlife management because they frequently contain cavities and they provide foraging sites and hunting perches (Conner et al 1975;Scott et al 1977;Evans and Conner 1979;Mannan et al 1980;Brawn et al 1982;Raphael and White 1984;Sedgwick and Knopf 1986;Rosenberg et al 1988;McClelland and McClelland 1999). Scott et al (1977) reported that snags provide essential habitat for 85 North American bird species that excavate cavities, use natural cavities, or use cavities excavated by other species. Bats roost in tree cavities and under exfoliating bark of snags (Menzel et al 2002).…”
Section: Introductionmentioning
confidence: 99%